Communication for Distributed Renewable Generations (DRGs): a review on the penetration to Smart Grids (SGs) - Islam, Syed Z; Mariun, Norman; Hizam, Hashim; Othman, Mohammad Lutfi; Mohd Radzi, Mohd Amran; Haniff, Mohd Nizal; Zainal Abidin, Izham
The use of energy in the domestic and industries lead to the pollution mainly due to the greenhouse gas emissions as well as pressure to replace the scarce fossil-fuel based energy. These contribute to the urgency towards the deployment of Renewable Energy (RE) and concurrently, the optimization of the existing energy distribution via Smart Grids (SGs). However, the present SGs implementation is still in their maturing stages especially in developing countries and yet to be extensively deployed due to many challenges. One of them is to develop robust, scalable and secured communication system between the Distributed Renewable Generations (DRGs) and the SGs. Improvement in the communication system definitely will increase the efficiency of both the existing energy management as well as the feeding system between the relatively low output DRGs to the SGs. In this paper, first we discussed DRGs especially solar Photovoltaic (PV) and wind generations along the suitable areas to mitigate weather uncertainty. Then a review on communication network architecture and Energy Management System (EMS) for integrating DRGs to the grid is presented. A comparison among the network technologies were also done to determine the robustness and efficiency of the network communication in terms of SGs.